Laparoscopic triple neurectomy as a treatment for chronic postoperative inguinal pain: a case report - Castillo, Antonio de Jesus Rodriguez; Muñoz, Carlos Alberto Peña; Juarez, Jose Angel Ibarra; Diaz , Jesús Guillermo Verástegui (International Surgery Journal, 2025)
Chronic postoperative inguinal pain is a potential complication following lower abdominal wall surgeries, particularly hernia repairs. When the pain is neuropathic and refractory to conservative treatment, surgical neurectomy may offer definitive relief. We report the case of a 56-years-old woman with severe right inguinal pain persisting six years after open inguinal hernia repair. The pain was burning in nature, radiated to the pubic region and significantly limited her daily activities. Clinical examination and dermatomal mapping confirmed involvement of the iliohypogastric, ilioinguinal and genitofemoral nerves. After conservative therapy failed, a laparoscopic triple neurectomy was performed through a transabdominal approach. Postoperative recovery was favorable, with progressive symptom relief and complete pain resolution (VAS 0/10) at two months. Laparoscopic triple neurectomy can be an effective and minimally invasive option for patients with chronic neuropathic inguinal pain unresponsive to medical management. Accurate diagnosis and patient selection are key to achieving optimal outcomes.